Small Urban Green Roof Plots Near Larger Green Spaces May Not Provide Additional Habitat for Birds - Partridge, Dustin R.; Clark, J. Alan (Frontiers in Ecology and Evolution, 2022)
Global wildlife populations are in decline, in part, due to urbanization. However, in urban landscapes, green infrastructure such as green roofs are being created to provide habitat for wildlife. Green roof isolation, planting heterogeneity, and size can all influence wildlife biodiversity, as may the age of a green roof. When new habitat is created, wildlife use of these new habitats is expected to increase over time. To test this expectation for birds, we monitored bird activity prior to and after installation of small green roof plots on six buildings located within New York City parks. Contrary to expectations, bird activity and bird species richness did not increase after green roof plot installation, nor did they increase over a period of 4 years following installation. These unexpected results may reflect the relatively small size of the plots or the fact that the plots were on buildings located within urban parks. Bird activity and bird species richness varied widely between roofs, and the composition of rooftop bird species may have been more influenced by the characteristics of the surrounding landscapes than the presence of the green roof plots. These findings suggest that small urban green roofs within a larger and, potentially, higher quality habitat may not provide additional habitat for foraging birds. Urban green roofs have numerous ecological and environmental benefits, but the size and characteristics of landscapes surrounding a green roof need to be considered when installing green roofs as wildlife habitat.